Quality of life among diabetic patients in Ahmedabad, India - Kachhawala, Fatema; Sisodiya, Ashadevi; Patel, Vaibhavi (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes, affecting 422 million people worldwide, with India having the second-largest diabetic population. India accounts for 1 in 7 of the global diabetic population and 63% of all deaths from NCDs. In Gujarat, diabetes prevalence is 16% in women and 17% in men. Quality of life (QOL) includes physiological, psychological, social, and spiritual satisfaction, is a key factor in disease management. Assessing QOL helps identify patient needs, evaluate treatment regimens, and improve health management. Methods: We conducted a community based cross-sectional study among diabetic patients using a Short Form 36 V2 to measure QOL of diabetics aged >18 years. In-person interviews were conducted with 310 diabetic patients from 30 UHCs of Ahmedabad Municipal Corporation that were chosen by cluster sampling. Data was analysed using suitable statistical parameters. Results: The study included 160 male and 150 female diabetic patients, with a mean age of 55.46±9.85 years and mean diabetes duration of 5.69±3.44 years. The mean QOL score was 71.37±18.14, with males reporting higher QOL than females. Advanced age, longer diabetes duration, sedentary lifestyle, comorbidities, and complications were associated with lower QOL. Higher education, nuclear family type, higher socio-economic status (SES) and regular physical activity improved QOL. No significant association was found between QOL and religion, occupation, marital status, diet type, overcrowding, or addiction. Conclusions: Significantly associated variables with QOL included Age, gender, education, type of family, Socioeconomic status, lifestyle, physical activity, comorbidity, duration and complication of diabetes.